The duration of Mediterranean diet affects the levels of the lipid profile in dyslipidemia patients - Handayani, Dewi R; Septiadi, Endry; Inayati, Iis; Pratiwi, Siska T; Anugrah, Rifal A; Rohman, Nur M; Prawira, Achmad H; Rais, Muhammad A (ACTA Medical Health Sciences, 2022)
Dyslipidemia is a lipid metabolism disorder that indicates abnormal levels of lipid profile in plasma. The most notable lipid profile abnormalities include increased levels of total cholesterol, low-density lipoprotein cholesterol (LDL), triglycerides, and a decrease in high-density lipoprotein cholesterol (HDL). One of the non-pharmacological management for dyslipidemia is diet modification with the Mediterranean diet. This study aims to determine the relationship between the duration of the Mediterranean diet and lipid profile levels in Prolanis patients who experience dyslipidemia in a clinic in Bandung. The research method was analytical with cohort observations. Sampling was done by consecutive sampling. Subjects in this study were 30 dyslipidemic patients who followed a Mediterranean diet and were examined for lipid profile levels in the first and third months. Data on total cholesterol, LDL, HDL, and triglycerides were analyzed using the T-dependent test. Total cholesterol and Triglycerides decreased significantly, and HDL increased significantly in the first and third month. The duration of the Mediterranean diet shows a reduction effect of total cholesterol, LDL, triglycerides and significantly increase HDL in patients with dyslipidemia because the recommended foods are high in monounsaturated fatty acids (MUFA) and polyunsaturated fatty acids (PUFA), which can correct abnormalities in lipid profile levels. DOI : 10.35990/amhs.v1n2.p64-70 REFERENCES Anwar TB. Dislipidemia Sebagai Faktor Resiko Penyakit Jantung Koroner. 2006;1–10. Wahjuni S. Dislipidemia menyebabkan stres oksidatif ditandai oleh meningkatnya malondialdehid. Bali: Universitas Udayana; 2015. hlm. 1–109. Hamam F. Dyslipidemia and related risk factors in a Saudi university community. Food Nutr Sci. 2017;8(1):56–69. Badan Penelitian dan Pengembangan Kesehatan Kementerian Kesehatan RI. Riset Kesehatan Dasar (RISKESDAS). Jakarta: Kemenkes RI; 2013. Labibah Z, Anggraini DI. Diet Mediterania dan manfaatnya terhadap kesehatan jantung dan kardiovaskular. J Majority. 2016;5:1–3. Estruch R. Anti-inflammatory effects of the Mediterranean diet: The experience of the PREDIMED study. Proc Nutr Soc. 2010;69:333–340. Sofi F, Macchi C, Abbate R, Gensini GF, Casini A. Mediterranean diet and health. Ann Ist Super Sanita. 2013;39:335–342. Tuttolomondo A, Simonetta I, Handayani DR, Daidone M, Mogavero A, Ortello A, Pinto A. Metabolic and vascular effects of the Mediterranean diet. Int J Mol Sci. 2019;20(19). John MF, Adam. Dislipidemia. Dalam: Sudoyo AW, dkk, editor. Buku Ajar Ilmu Penyakit Dalam. Jilid III, Edisi IV. Jakarta: Balai Penerbit FKUI; 2006. hlm. 2556–2557. Wiyono P. Penatalaksanaan dislipidemia pada diabetes melitus. 2003;1–11. Corradi PF, Agrawal N, Gumaste N, Goldberg IJ. Principles of Diabetes Mellitus. Principles of Diabetes Mellitus. 2016;1–19. Anneke R, Sulistiyaningsih. Review: Terapi herbal sebagai alternatif pengobatan dislipidemia. Farmaka. 2018;16:213–221. Rhee E, Kim HC, Kim JH, Lee EY, Kim BJ, Kim EM, et al. 2018 Guidelines for the management of dyslipidemia and cardiovascular disease in Koreans. Korean J Intern Med. 2019;34(4):723–771. Lestari A, Handini MC, Sinaga TR. Faktor risiko kejadian dislipidemia pada lansia (Studi kasus kontrol pada lansia di Poli Lansia RSUD Bangkinang Kabupaten Kampar Tahun 2016–2017). J Ris Hesti Medan Akper Kesdam I/BB Medan. 2018;3(2):16. Steinberg D, Witztum JL. History of discovery: Oxidized low-density lipoprotein and atherosclerosis. Arterioscler Thromb Vasc Biol. 2010;30(12):2311–2316. Tautik S. Hubungan antara kadar estradiol dengan profil lipid. 2011;1:47. Nugraheni K. Pengaruh pemberian minyak zaitun ekstra virgin terhadap profil lipid serum tikus putih strain Sprague Dawley hiperkolesterolemia. J Ilmu Gizi. 2012;1:27. Mekki K, Bouzidi BN, Kaddous A, Bouchenak M. Mediterranean diet improves dyslipidemia and biomarkers in chronic renal failure patients. 2010;1:110–115. Pachyrrhizus B, Pada E, No JS. J Nutr College. 2014;3:573–579. Make Each Day Mediterranean. U.S. News and World Report; 2012. hlm. 1–11. Dernini S, Berry EM, La Vecchia C, Capone R. MedDiet4.0: The Mediterranean diet with four sustainable benefits. Public Health Nutr. 2016;20(7):1322–1330. Boucher JL. Mediterranean eating pattern. Diabetes Spectrum. 2017;72–76. American Diabetes Association. Widmer RJ, Flammer AJ, Lerman LO, Lerman A. The Mediterranean diet, its components, and cardiovascular disease. Am J Med. 2015;128(3):229–238. Nutrition Clinics for UW Medical Foundation. Mediterranean Food Guide. UW Health; 2019. hlm. 1–42. Meslier V, Laiola M, Roager HM, De Filippis F, Roume H, Quinquis B, et al. Mediterranean diet intervention in overweight and obese subjects lowers plasma cholesterol and causes changes in the gut microbiome and metabolome independently of energy intake. Gut. 2020;69(7):1258–1266.